Potential Involvement of SCF-Complex in Zygotic Genome Activation During Early Bovine Embryo Development - Benesova, Veronika; Kinterova, Veronika; Kanka, Jiri; Toralova, Tereza (Methods in molecular biology, 2017)
Proper timing of degradation of maternal protein reserves is important for early embryonic development. The major modification that triggers proteins to degradation is ubiquitination, mediated by ubiquitin-proteolytic system. We focus here on Skp 1-Cul 1-F-box complex (SCF-complex), E3 ubiquitin-ligase, a part of ubiquitin-proteolytic system, which transfer ubiquitin to the substrate protein. We describe in this chapter the methods for the characterization of the expression profile of mRNA and protein of invariant members of SCF-complex and for the definition of SCF-complex activity.
Keywords: Cattle; Animals; skot; Female; proteolýza; Gene Expression Regulation, Developmental; ženské pohlaví; proteinligasy komplexu SCF; stanovení celkové genové exprese; ubikvitinligasy; Embryonic Development; aktivace transkripce; SKP Cullin F-Box Protein Ligases; zvířata; embryonální vývoj; Ubiquitin-Protein Ligases; vývojová regulace genové exprese; Transcriptional Activation; Gene Expression Profiling; Proteolysis